LEARNING PROCESS IN VIRTUAL CLASSROOMS AND ITS RELATIONSHIP WITH RELATIONSHIP WITH THE SATISFACTION OF THE STUDENTS - JAUREGUI-VILLAFUERTE, CÉSAR (2024)
THE OBJECTIVE OF THIS RESEARCH WAS TO DETERMINE THE LEVELS OF STUDENT SATISFACTION IN THE FACULTY OF ECONOMIC SCIENCES DUE TO THE SUDDEN VIRTUALIZATION OF TEACHING IN THE CONTEXT OF THE COVID-19 PANDEMIC. THE TYPE OF RESEARCH WAS BASIC, WITH A DESCRIPTIVE LEVEL - CORRELATIONAL AND CROSS-SECTIONAL. A VIRTUAL QUESTIONNAIRE WAS APPLIED, BASED ON A LIKERT-TYPE SCALE, PREVIOUSLY VALIDATED BY EXPERT JUDGMENT WITH A CRONBACH'S ALPHA RELIABILITY OF 0.862. THE POPULATION CONSISTED OF 1,271 STUDENTS ENROLLED IN THE ACADEMIC SEMESTER 2021-I IN THE FACULTY OF ECONOMIC SCIENCES, THE SAMPLE WAS MADE UP OF 202 STUDENTS AND THE SAMPLING WAS PROBABILISTIC. THE FOLLOWING CONCLUSIONS WERE REACHED: (A) IT WAS IDENTIFIED THAT VIRTUAL EDUCATION AND VIRTUAL LEARNING RESOURCES ARE RELATED TO STUDENT SATISFACTION. (B) STUDENT LEARNING WAS IDENTIFIED AS BEING RELATED TO STUDENT SATISFACTION. (C) IT WAS IDENTIFIED THAT VIRTUAL SKILLS ARE RELATED TO STUDENT SATISFACTION. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.